2007
DOI: 10.4049/jimmunol.179.6.3982
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Tumor Necrosis Factor Generated during Lethal Plasmodium Infections Impairs Dendritic Cell Function

Abstract: Dendritic cells (DCs) initiate innate and adaptive immune responses including those against malaria. Although several studies have shown that DC function is normal during malaria, other studies have shown compromised function. To establish why these studies had different findings, we examined DCs from mice infected with two lethal species of parasite, Plasmodium berghei or P. vinckei, and compared them to DCs from nonlethal P. yoelii 17XNL or P. chabaudi infections. These studies found that DCs from only the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…It has been suggested that TNF-a may contribute to DC activation and concomitant down-regulation of antigen presentation [14].…”
Section: Tnf-a Is Not Responsible For the Reduction In Antigen Presenmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that TNF-a may contribute to DC activation and concomitant down-regulation of antigen presentation [14].…”
Section: Tnf-a Is Not Responsible For the Reduction In Antigen Presenmentioning
confidence: 99%
“…It has been suggested that TNF-a may contribute to DC activation and concomitant down-regulation of antigen presentation [14]. To test this possibility, we infected WT B6 or TNF-a-deficient mice with P. berghei parasites and then examined the proliferation of CD8 1 OT-I T cells in response to immunization with OVAcoated spleen cells (Fig.…”
Section: Tnf-a Is Not Responsible For the Reduction In Antigen Presenmentioning
confidence: 99%
See 1 more Smart Citation
“…In playing such a central role in immunity, it is not surprising that the function of DCs is targeted by the parasite. Indeed, several studies in both humans (5,6) and mice (7)(8)(9)(10)(11)(12)(13)21) have documented changes in DC function in response to Plasmodium. In contrast, other reports have found fully functional DCs when exposed to parasites (14 -20).…”
mentioning
confidence: 99%
“…This DC phenotype may be maintained over the entire course of infection with nonlethal strains of Plasmodium [45], although it is unclear how lethal and nonlethal strains differ with respect to the immune response they generate, and the influence of dose. Later, when parasite densities are peaking, DCs may become refractory to TLR and other signaling events, possibly due to overstimulation or due to TNF-α [46,47], thus abrogating IL-12 and TNF-α secretion, and as capacity to produce IL-10 increases. While secretion of IL-10 may reduce inflammatory responses, a desirable effect when linked to clinical immunity [1], specific immune responses to malaria antigens as well as to other infections and vaccines may be reduced.…”
Section: Dendritic Cells and Malariamentioning
confidence: 99%